On Fuzzy Derivation of Ideals of BF-Algebras - Gerima Tefera Dejen; Tsige Gebrekidan (Journal of Mathematics)
The concept of fuzzy derivation of ideals of BF algebra is introduced. In addition, fuzzy left derivation of ideals of BF-algebras and fuzzy right derivation of ideals of BF- algebra are discussed. We also investigated fuzzy left (right) derivation of Cartesian product of ideals of BF-algebra. We initiated the idea of level cut in fuzzy derivation of ideals of BF-algebra and showed that the intersection of any set of left (right) fuzzy derivations of ideals of BF-algebra is also fuzzy left (right) derivation of ideals of BF-algebra.